Active vibration control using piezoelectric actuators employing practical components. (November 2019) - Williams, D; Haddad Khodaparast, H; Jiffri, S; Yang, C
Unwanted vibrations are a common occurrence within structures and systems, and often pose a threat to their integrity or functionality. This research aims to seek a solution to attenuate the vibrations experienced within a link of a system using active vibration control with piezoelectric patches as actuators, whilst avoiding the use of large and expensive equipment which would contravene with the common objective of maintaining the smallest mass possible of the system. Previous research has employed large and expensive equipment as the controller, with sensors often only being able to measure the vibrations of the structure along one axis; this research aims to address these issues. The choice of utilizing the small, lightweight, and low-cost Raspberry Pi 3 combined with petite, mountable sensors and actuators was made based upon the greater practicality that the controller, sensors, and actuators exhibit, allowing for their use in a wide variety of applications. An analytical model of the structure was created based on Euler–Bernoulli beam theory and validated through the modal parameters and the frequency response obtained from a finite element model and experimental data. A controller was then designed and applied to the analytical model to attenuate the vibrations along the link, and then the same design was implemented within the Raspberry Pi 3, and experimental studies were carried out. The introduction and effectiveness of a purposeful time delay within the controller was explored within the experimental and analytical studies, with the intention of counteracting unfavorable results produced by the control system. The results of the experiment proved the control design to be effective for a range of frequencies that included the first natural frequency of the link, and validated the analytical model including the control design.